THE IMPACT OF HANDS ON PUMPING ON THE LEVEL OF BREAST MILK PRODUCTION ON POST PARTUM MOTHERS - Leni Marlina; Dora Samaria; Theresia Theresia (Universitas Pelita Harapan, 2019)
The exclusive breastfeeding in Indonesia has not yet reached the national level target. Data from Private Hospital in West Jakarta found that there were only 60% of mothers who gave exclusive breast feeding in 2016, 38% of whom said they were unsuccessful due to low breast milk. The method that can be used to increase milk production is Hands on Pumping (HOP) technique, HOP is a technique of flushing the breast milk by relying on the strength of our thumb and index finger. To observe the effect of HOP on breast milk production in post partum mothers. We employed a quasi experimental design with pre and post test design, with the control group. The sample size was 68 mothers post multiparous partum with criteria 34 as the HOP experimental group and 34 post partum mothers as the control group (without HOP). On the third day of the intervention group there was a significant increase in breast milk production from the first day. The experimental group received HOP intervention (34 mothers) with a rise of 121.08 ml. This means that there is a difference in milk production before and after treatment. On the third day, the results of the p value are 0,000, with p value <0.05, which brought to the conclusion that there was an influence of HOP on breast milk production. HOP can significantly increase milk production. Next researcher is recommended to conduct similar research by paying attention to other factors that also affect breast milk production, such as psychological, nutrition, maternal breast conditions, and hormones.